Pemahaman Mahasiswa Terhadap Ungkapan Bahasa Arab Yang Sering Digunakan di Media Sosial - Zali, Muhammad; Nurul Azkia, Aisha; Zahra Harahap, Atika; Sofia, Azyka; Manurung, Bela Wahyuni; Br Sitorus, Dini Sastra; Nazwa, Khairin; Cornelia Susilo, Maurinda; Luthfiyyah, Mahirah Azzah; Aini Lubis, Nazwa Septi; Khoiriyah, Nurul (PT. Alahyan Publisher Sukabumi, 2025)
This study aims to examine the extent to which students understand Arabic expressions frequently used on social media and how these media play a role in the learning process. In the digital era, social media such as YouTube, Instagram, and TikTok have become popular means for students to learn Arabic flexibly and interactively. This study uses a qualitative method with a literature study approach. Data were obtained from various secondary sources such as scientific journals and previous research results. The results of the study show that social media can increase motivation, enrich vocabulary, and strengthen students' language skills, especially in listening and speaking. However, there are also challenges such as distraction from entertainment content, dependence on technology, and limitations in contextual and cultural understanding. Therefore, a balanced learning strategy is needed between the use of social media, teacher assistance, and the development of critical digital literacy so that Arabic language learning remains contextual and meaningful. In conclusion, social media has great potential as an effective Arabic language learning medium if used wisely and in a targeted manner.